Assessment of the M&E system’s contribution to Gauteng Tourism Authority’s (GTA) programmes outcomes - Hamilton, Alecia Lindse’ (University of the Witwatersrand, Johannesburg, 2024)
A major challenge for governments is to become more effective, therefore the South African government has backed monitoring and evaluation (M&E) as its processes can assist the public sector in assessing its performance. Components which set M&E apart from other management systems is the feedback and learning component which is instilled in the M&E system, these components assist decision makers to make evidence-based informed decision. The South African government has implemented an overarching M&E system in which all three spheres must adhere to. By implementing the M&E system it exercises the principles of good and developmental governance, this is monitored by oversight bodies which enforces compliance. The study looks at the case study of Gauteng Tourism Authority (GTA), the public entity is the tourism implementing arm of the Gauteng Department of Economic Development. GTA has three budgeted programmes by which it tracks and assesses performance through the overarching M&E system. The objective of the study is to understand how the implemented M&E system within the South African public sector has assisted the GTA in meeting its desired outcomes through its implemented three programmes. The study concludes by recommending the importance of effectively institutionalising M&E by educating employees at all levels about the value and purpose of M&E which will assists with the identified finding, namely the usage of monitoring and evaluation interchangeably and the over- reliance on one component to the other hinders the M&E systems effectiveness. The methodological approach draws from the constructivist and interpretivism research paradigms. The two approaches are often combined in a qualitative research strategy, this is considered suitable for the study as it allows participants who were interviewed to fully share their knowledge and experiences. The research design utilised a case study of the GTA, the research methods included primary and secondary which included supporting literature. A qualitative analysis of the findings focused on the themes that emerged from the study and the way it was conceptualized.
A research report submitted in fulfillment of the requirements for the Master of Management, In the Faculty of Faculty of Commerce, Law and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Monitoring and Evaluation; Performance Management System; Result-based Management system; public sector; oversight bodies; institutionalisation; compliance; SDG-8: Decent work and economic growth